RELIGIOUS SYSTEM IN INDIGENOUS COMMUNITIES OF BENA VILLAGE - I Gusti Ngurah Jayanti (Pusbindiklat - LIPI, 2012)
Bena Village is a traditional village that still holds its customs, tradition and religion. The belief to worshipof ancestral spirits still exists although some people have been as a Christian. The problem of this study is how thereligious systems of indigenous communities in Bena village. The method of the study is interpretive descriptivequalitative method. In the result discussion of the study explained that the worship of ancestral spirits is reflectedin the various religious rituals procession. There are always the power of ancestral spirits in each ritual. Start fromthe toothfilling ceremony, building a house ceremony, manufacture of Ngadhu and Bhaga ceremony, those all weredone with ritual worship of ancestral spirit.Keywords: System of Religion, Life cycle, Symbols